1624 Myoclonus dystonia: a clinical and genetic description. Issue 3 (9th February 2012) - Peall, K; Waite, A J; Kurian, M A; Hedderly, T; Smith, M; Lin, J P; Warner, T T; Pall, H; Chinnery, P; Whone, A; Owen, M J; Blake, D J; et al.
Abstract : Background: Myoclonus Dystonia Syndrome (MDS) is a childhood onset movement disorder involving trunk and upper limb myoclonus and dystonia of the neck and hands. Psychiatric co-morbidity has also been described and most cases are due to mutations in the epsilonsarcoglycan gene (SGCE). Aims: We aimed to establish a cohort of MDS cases to identify the rate and type of SGCE mutations and to systematically establish the psychiatric and motor features. Methods: We have collected 80 unrelated patients with clinically suspected myoclonus dystonia syndrome. Clinical information was collected by clinical examination using standardised questionnaires or from the referring clinician. SGCE mutations were identified using Sanger sequencing and multiplex ligation-dependent probe amplification (MLPA). Results: Conclusion: 14/80 samples have SGCE mutations. Mutation carriers had features consistent with the proposed diagnostic criteria, and four families were identified with additional lower limb dystonia. 8/14 families had concurrent psychiatric disease. Genetic mutations included single exon and whole gene deletions, splice site mutations and most commonly, premature stop codon mutations. There is no clear genotype/phenotype relationship with the exception of dysmorphic features in some of the whole gene deletion cases.